Comparison of the rapid emergency medicine score and rapid acute physiology score in non-surgical emergency department patients - Yadav, Jyoti Kumari; Mansuri, Md. Islam; Yadav, Abhiyendra Khirhari; Thakur, Nishant (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Emergency medical admissions pose a significant burden, necessitating effective risk stratification tools for mortality estimation. The current study aims to compare the prognostic accuracy of existing severity scoring systems, Rapid Acute Physiology Score (RAPS) and Rapid Emergency Medicine Score (REMS) in estimating mortality risk among non-surgical patientsMethod: This cross-sectional study, conducted at a teaching Hospital in Nepal for three months. Data collection involved clinical assessments and estimating RAPS and REMS scores. Chi-square test and correlation analysis were employed to assess the significance of severity scores and their association with clinical parameters. The predictive accuracy of RAPS and REMS for in-hospital mortality was determined.Result: The study encompassed 154 patients admitted to the emergency department and moved to Medicine, ICU, Emergency Room, and ENT departments. Both scores had similar overall performance, but REMS showed slightly higher sensitivity (95.93%) compared to RAPS (85.37%). Positive correlations were observed between REMS and age (p